Automation of Directory Assistance - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2025)
The Journal revisits two historic papers from 1981/82 that describe a successful trial in Sydney of a computer-based system to automate the Directory Assistance manual card records in Australia.  The trial led to the implementation of a national Directory Assistance system which provided productivity improvements but fell short of the performance achieved by similar systems in the USA.